Electrochemical studies on chromium doped SrTiO3 for supercapacitor applications - D.K. Sharma; S. Sain; G. Maity; A. Thomas; R. Kumar; S. Dhar; H.S. Arora; B. Babu; S.S. Roy (Nano Trends, 2024)
Perovskite oxides have garnered significant attention as potential active materials for supercapacitor applications. Recently, metal-doped perovskite oxides have gained prominence due to their potential to provide a synergistic blend of electrical conductivity, substantial electrochemical active surface area, and robust electrochemical activity. In this study, we systematically investigate the electrochemical properties of strontium titanate oxide (SrTiO3, STO) and chromium-doped strontium titanate oxide (Cr-STO), synthesized via the solid-state reaction method. Various material characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS), are employed to examine the crystal structure, morphology, and chemical composition of these samples. Notably, Cr-STO demonstrates an approximately twentyfold increase in electrochemical surface area compared to pristine STO, resulting in enhanced anion storage capabilities when employed in alkaline 3 M KOH aqueous electrolytes. Detailed electrochemical kinetic studies reveal an augmented pseudocapacitive behavior in Cr-STO, with a more pronounced diffusive nature compared to pristine STO. Furthermore, symmetric supercapacitors fabricated with Cr-STO electrodes exhibit excellent electrochemical performance, maintaining over 93 % of their initial capacity after 10,000 charge-discharge cycles at a current density of 1 A g−1. These findings highlight the significant potential of chromium-doped strontium titanate oxide as a valuable contribution to the ongoing pursuit of novel material for supercapacitors.